The Effect Of Health Education On The Knowledge And Attitudes Of Adolescent Health Cadres About Table Fe Consumption In Sma N 1 Kediri Regency - Erni Rahmawati; Anas Tamsuri; Bambang Wiseno; Ratih Kusuma Wardhani (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
Anemia in young women has an impact on impaired physical growth, decreased endurance, decreased intelligence, reduced learning achievement and concentration and always appears lethargic, pale and uninspired. The purpose of the study was to determine the influence of health education on the knowledge and attitudes of Adolescent Health Cadres (KKR) at SMA N 1 Kediri Regency. The research method used is quasi-experimental with a one group pretest-posttest design. The sample in this study was 80 students of SMA N 1 Kediri Regency. The variables in the study were independent variables (health education interventions about fe tablet consumption) and dependent variables (knowledge and attitudes). The research measuring instruments used questionnaires and analyzed by univariate analysis, normality test with one kolmogorov-smirnov test, and bivariate analysis using wilcoxon test. The results showed that there was an influence of health education on the knowledge (p = 0.000) and attitudes (p = 0.000) of adolescent health cadres (KKR) about the consumption of Fe tablets. The health promotion organizing team needs to prioritize effective methods and attract students' interest in following the material provided. Keyword: Knowledge, Attitudes, KKR